(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This study is to determine the strategy of development of tourism sector of Culture and Tourism District Talaud islands. Department of Culture and Tourism Talaud district has an important role in developing the tourism sector and is responsible for the management and maintenance of tourism potential as well as the facilities and infrastructure that exist. One example of the ineffectiveness of the strategy Department of Culture and Tourism in developing the tourism sector is, there are many sights that have not been managed properly, also the absence Determination levy entry fee for each visitor who comes in location, as well as limitations and lack of facilities supporting tourism becomes one of the factors that hinder tourism management. Lack of promotion and lack of awareness and community participation in the tourism sector to make tourism in Talaud Regency difficult to develop. This study uses Qualitative Research Methods SWOT analysis techniques through interviews with 10 Informants, observation and document tracking instrument assisted an additional form of interview guidelines using data analysis techniques of data reduction, data presentation, and of the conclusion. Based on the research results through a SWOT analysis. The following are the results of the analysis: Department of Culture and Tourism Talaud district has the strength of the tourism sector will be an asset that is more wealth of art and culture and tourism asset, weaknesses in the Department of Culture and Tourism is not optimal promotion and tourism marketing, the opportunities that exist in the Department of Culture and Tourism in developing the tourism sector in the District Talaud is stakeholder support tourism and culture, especially the Provincial and National strong in the Development of Culture and Tourism areas, where as the challenges faced by the Department of Culture and Tourism in developing the tourism sector is the level of competition among the regions in which travel product offerings on the above conclusions, are suggested to be cooperation between, the Department of Culture and Tourism with the private sector or investors, then the Office Culture and Tourism and the local government must facilitate all the needs of tourism, especially in terms of facilities and infrastructure and training-training and promotion. Key Words: the role of the Agency in the implementation of regional staffing mutations.